Media Read & Play Berbasis Game Edukasi Untuk Menumbuhkan Minat Baca di Kelas 2 SD - Afifah, Rostanti Nurul; Rosidin, Odin; Yuliana, Rina (Universitas Muhammadiyah Magelang, 2022)
Most of the Indonesian population has not made reading activities a basic need. Several factors contribute to the low interest in reading in Indonesia, namely the growing development of technology, making the current generation more busy with gadgets than reading books, this is not in line with the progress of learning media innovation. The purpose of this study was to determine (1) the process in developing Educational Game-Based Read & Play media to foster reading interest, (2) the feasibility of Educational Game-Based Read & Play media to foster reading interest, (3) students' responses to the implementation of Read & Play Educational Game-Based Play to foster interest in reading. The research method is Research and Development (R&D) using the 4D model by Thiagarajan which consists of 4 stages, namely define, design, develop, and disseminate. The results of research at SDN Kutabaru 1 in class 2 with a total of 31 students showed that Educational Game-Based Read & Play media was very feasible to foster students' interest in reading. This is proven by the validation results from two media experts with a percentage of 93.5% in the category